Patients' characteristics and mortality in urgent/emergent/salvage transcatheter aortic valve replacement: insight from the OCEAN-TAVI registry. Issue 2 (14th December 2020) - Enta, Yusuke; Miyasaka, Masaki; Taguri, Masataka; Tada, Norio; Hata, Masaki; Watanabe, Yusuke; Naganuma, Toru; Yamawaki, Masahiro; Yamanaka, Futoshi; Shirai, Shinichi; Ueno, Hiroshi; Mizutani, Kazuki; et al.
Abstract : Objectives: Patients' backgrounds and clinical outcomes in urgent/emergent/salvage transcatheter aortic valve replacement (Em-TAVR) remain unclear. We investigated patient characteristics and the mortality in Em-TAVR and the predictors for the need for Em-TAVR. Methods: We consecutively enrolled 1613 patients undergoing TAVR for severe aortic stenosis between October 2013 and July 2016 from the Optimised transCathEter vAlvular interventioN (OCEAN)-transcatheter aortic valve implantation (TAVI) registry. The urgency was based on the European System for Cardiac Operative Risk Evaluation II. Urgent, emergent or salvage were included with the Em-TAVR group and elective with the El-TAVR group. Results: Em-TAVR was observed in 87 (5.4%) patients. A higher Clinical Frailty Scale (CFS), peripheral artery disease (PAD), hypoalbuminaemia, reduced left ventricular ejection fraction (LVEF) and preoperative at least moderate mitral regurgitation (MR) predicted the need for the Em-TAVR by the multivariate logistic regression analysis. The Em-TAVR group had the higher Society of Thoracic Surgeons Score (13.7 (IQR 8.2–21.0) vs 6.5 (IQR 4.6–9.2); p<0.001) and higher 30-day mortality (9.2% vs 1.3%; p<0.001) than the El-TAVR group. Accordingly, Kaplan-Meier analysis showed that the cumulative mortality was higher in the Em-TAVR group than that in the El-TAVR group (log-rank; p<0.001). However, Em-TAVR did not predict mortality in the multivariate Cox regression analysis. Conclusions: Em-TAVR was performed in 5.4% of patients. Higher CFS, PAD, hypoalbuminaemia, reduced LVEF and preprocedural MR predicted the need for Em-TAVR. Em-TAVR was not a predictor for mortality in the multivariate analysis, suggesting that it is a reasonable treatment option.